Fresnel Lens Solar-Pumped Laser with Four Rods and Beam Merging Technique for Uniform and Stable Emission under Tracking Error Influence - Bruno D. Tibúrcio; Dawei Liang; Joana Almeida; Dário Garcia; Miguel Catela; Hugo Costa; Cláudia R. Vistas (Energies, 2023)
Significant numerical improvements in Fresnel lens Nd:YAG solar laser collection efficiency, laser quality factors and tracking error compensation capacity by two Fresnel lenses as primary solar concentrators are reported here. A Nd:YAG four-rod side-pumping configuration was investigated. The four-rod side-pumping scheme consisted of two large aspherical lenses and four semi-cylindrical pump cavities, where the Nd:YAG laser rods were placed, enabling an efficient solar pumping of the laser crystals. A 104.4 W continuous-wave multimode solar laser power was achieved, corresponding to 29.7 W/m2 collection efficiency, which is 1.68 times that of the most efficient experimental Nd:YAG side-pumped solar laser scheme with heliostat–parabolic mirror systems. End-side-pumped configuration has led to the most efficient multimode solar lasers, but it may cause more prejudicial thermal effects, poor beam quality factors and a lack of access to both rod end-faces to optimize the resonant cavity parameters. In the present work, an eight-folding-mirror laser beam merging technique was applied, aiming to attain one laser emission from the four laser rods that consist of the four-rod side-pumping scheme with a higher brightness figure of merit. A 79.8 W multimode laser output power was achieved with this arrangement, corresponding to 22.7 W/m2. The brightness figure of merit was 0.14 W, being 1.6, 21.9 and 15.7 times that of previous experimental Nd:YAG solar lasers pumped by Fresnel lenses. A significant advance in tracking error tolerance was also numerically attained, leading to a 1.5 times enhancement in tracking error width at 10% laser power loss (TEW10%) compared to previous experimental results.